Securing WSN and MANET communication for military operation based on ECC algorithm - Rizal Mohd Isa, Mohd; Naim Abdullah, Muhammad; Zakaria, Omar; Nazri Ismail, Mohd; Adib Khairuddin, Mohammad; Maskat, Kamaruzaman; Afizi Mohd Shukran, Mohd; Fahmi Mohamad Amran, Mohd (International Journal of Engineering and Technology, 2019)
The key aspect in military operations is keeping the communication stable and secure as possible. Connection downtime should be avoidance as it creates miscommunication between Military officers hence would impact on the targeted mission. The complexity of the terrains such as in the jungle area, contribute to a great challenge in maintaining the communication amongst military officer. Wireless Sensor Network (WSN) and Mobile Ad-Hoc Network (MANET) have been chosen to support on the communication platform between military officers for its capability in maintaining the stability of the connection lines. The confidential of the shared data amongst the military officers are also crucial which could be stolen and tampered by outsiders. The Elliptic Curve Cryptography (ECC) algorithm is selected for its ability to provide high security with small key size. This paper proposed a new framework in securing the WSN and MANET communication based on ECC algorithm for Military operations. The contribution of this research will not only towards military operations but not limited to Search and Rescue (SAR) operations as well. Â Â